RISK AWARENESS AND EXISTING KNOWLEDGE OF PEOPLE ABOUT BIOMEDICAL TECHNIQUES - DEVIKA S.,; RASHI K.,; SHALAGHA.Y.,; RAJAM.C.,; RAJENDRAN.N., (International Journal of Pharma and Bio Sciences, 2014)
Biomedical techniques are the latest techniques which are being used to treat and monitor many diseases, e.g. cancer, diabetics etc. and they are quite advanced and different from traditional techniques. They may have many benefits over traditional/existing techniques, but they may also have certain limitations. To overcome any such risks and limitations, biomedical research is being carried out either to improve or identify new approaches. The objectives of this research work were to know the awareness among people about these biomedical techniques, their benefits and risks involved and the extent of their preference towards the latest biomedical techniques. From the results of the preliminary survey, it was found that maximum numbers of participants were only aware about the conventional techniques that are being used to treat cancer, diabetes and asthma. It was also found that only 44% of the population was aware about tissue engineering. Among the population studied 77% of the people were not aware about risks involved in biomedical techniques, but many of them preferred benefits generated by biomedical approaches over the possible risks associated with them. However, this preliminary survey conducted with a small population suggested that awareness seem to be poor about biomedical techniques and there is an urgent need for awareness programs.